Description of the Implementation of Intravenous Infusion Treatment in the Internal Medicine Room - Rudi Kurniawan; Aas Rosidah; Elis Noviati; Andan Firmansyah; Fidya Anisa Firdaus (LPPM STIKes Muhammadiyah Ciamis, 2023)
Purpose: The goals of IV care are to maintain aseptic technique, prevent bacterial invasion of blood vessels, prevent infection, and observe the IV insertion site. Method: This research uses descriptive research with a quantitative approach. The sample from this research was 42 respondents, taken using G-Power statistical calculations. The population of this study was 42 respondents. March– April 2022 Results: It shows from 42 respondents that 20 actions are appropriate and 22 actions are not appropriate for infusion treatment in the disease unit in the Ciamis Regency Regional Hospital. Conclusion: Based on the survey conducted, there were no infusion treatments that were not carried out because they did not or did not have an SOP for infusion care at Ciamis Regional Hospital, so the results obtained were 20 actions in accordance with the SOP and 22 actions not in accordance with the SOP